Are living labs effective? Exploring the evidence. (August 2021) - Paskaleva, Krassimira; Cooper, Ian
Abstract: The main question addressed in this article is whether the evidence that is publicly available validates the claim that Living Labs are an effective means for promoting innovation. Owing to widespread promotion of their usefulness as a practical tool for pursuing innovation, Living Labs have enjoyed increasing attention from researchers, policy-makers and practitioners. But despite the booming interest in Living Labs – where innovation is generally perceived as taking place in real-life environments – their actual performance remains under-researched. It has yet to be demonstrated whether, in practice, Living Labs speed up the design of 'solutions' to societal challenges or the sharing of user value. This study aims to assess the existing evidence about whether they really deliver. A broadly based literature review was conducted to discover whether those initiating Living Labs report success – achieving the objectives/benefits they set themselves. Conclusions are drawn about whether the evidence is, at present, strong enough to warrant the promotion this approach receives. We suggest that, despite their 20-year history, the operationalisation of and outcomes from Living Labs are still poorly understood owing to paucity of published evidence, compounded by inadequate research design and insufficient attention to implementing and reporting performance evaluations. Highlights: Pioneering investigation of whether Living Labs actually deliver as promoted. Evidence base for their performance has yet to mature and be placed in public domain. Limited material published on innovation results achieved by using Living Labs. Living Labs' 'cradle to grave' cycle needs scrutiny to establish what does and does not work. Further evaluation needed of whether (and when) Living Labs deliver effective innovations.